PERAN MOTIVASI BELAJAR DAN KETERLIBATAN ORANG TUA DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR - Yulianti Kartika; Ida Ermiana; Darmiany (STKIP Subang, 2025)
This study aims to determine the role of learning motivation and parental involvement in improving the learning outcomes of third-grade students at SDN 2 Teruwai. This study uses a quantitative approach with a correlational design. The research subjects consisted of 12 third-grade students selected using total sampling technique. Data on learning motivation and parental involvement were collected through questionnaires, while data on learning outcomes were obtained from student evaluation scores. Data analysis techniques included descriptive statistics, classical assumption tests consisting of normality, multicollinearity, heteroscedasticity, and autocorrelation tests, as well as Pearson's correlation and multiple correlation tests using the SPSS program. The results of descriptive statistical analysis showed that student learning motivation, parental involvement, and learning outcomes were in the good category. The results of the normality test showed that all data were normally distributed, while the results of the multicollinearity, heteroscedasticity, and autocorrelation tests showed that the analysis model had met the classical assumptions. The results of the Pearson correlation test showed a strong and positive relationship between learning motivation and student learning outcomes as well as between parental involvement and student learning outcomes. Furthermore, the results of the multiple correlation test showed that learning motivation and parental involvement together had a very strong relationship with student learning outcomes, so it can be concluded that motivation.